Impact of Single vs Combination Anti-Hyperglycemic Drug Therapy on HbA1c Levels: A Cross-Sectional Study - Diatri, Devita; Rakhmawatie, Maya Dian (South East Asia Nursing Research, 2024)
Diabetes Mellitus (DM) is a long-term medical condition characterized by increased blood glucose levels caused by abnormalities in the insulin metabolism process. Various types of antihyperglycemic drugs are available, both as single and combination therapy. Recent research shows that single or combination therapy can impact glycemic control differently, especially when looking at changes in HbA1C levels.  This research is descriptive-analytical with a cross-sectional design using medical record data from Type 2 DM patients in the 2022-2023 period.  Data was analyzed using SPSS. In this study, there was a significant relation between single and combination anti-hyperglycemic drug therapy. Bivariate analysis showed that both single and combination therapy were associated with a reduction in HbA1C levels, with a p-value of 0.019. There is a correlation between HbA1C levels and single and combination therapy in type 2 DM patients at the Prolanis Clinic.